Atmospheric emissions of fine particle matter bound rare earth elements from industry - Jianghui Yun; Qiuting Yang; Chenyan Zhao; Changzhi Chen; Guorui Liu (Nature Communications)
Abstract Unintentional releases of rare earth elements (REEs), emerging environmental pollutants, from global industries contribute to atmospheric pollution. However, a gap remains regarding the recognition of REYs in industrial fine particulate matter (PM) as a primary source of atmospheric PM. Here, we identified the characteristic of REEs in PM from 114 large-scale industries covering 13 important sectors. Based on the derived emission factors, 13 industrial sources in China emit 136,914 kg of REEs annually, with cement, coal power and coking responsible for 105,226, 12,635, and 11,940 kg/year, respectively. Source-specific elemental profiles were achieved and can be used to allocate the sources of REEs in atmosphere. The average daily intake of REEs from industrial fine PM inhalation was 11.72 ng/(kg·day) for children and 7.41 ng/(kg·day) for adults, pivotal data for assessing health risks. This study is important for sustainable industrial development and human wellness.